2015
DOI: 10.1016/j.yexcr.2015.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic processing of the neuronal ceroid lipofuscinosis related lysosomal protein CLN5

Abstract: CLN5 is a soluble lysosomal glycoprotein. Deficiency in CLN5 protein causes neuronal ceroid lipofuscinosis, an inherited neurodegenerative lysosomal storage disorder. The function of CLN5 and how it affects lysosome activity are unclear. We identified two forms of the CLN5 protein present in most of the cell lines studied. The molecular mass difference between these two forms is about 4 kDa. The fibroblast cells derived from two CLN5 patients lack both forms. Using transient transfection, we showed one of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 37 publications
1
18
1
Order By: Relevance
“…We found that preproCLN5 and proCLN5 are type II transmembrane domain proteins while mature CLN5 (mCLN5) is within the lumen of organelles and localizes to the lysosomal compartment. A recent study also demonstrated a further processing step as mCLN5 is processed in the lysosomal compartment as leupeptin blocked this final processing step [41]. Next to determine whether mCLN5 was soluble or membrane bound, we performed a Na2CO3 extraction and found that a significant portion of mCLN5 is soluble.…”
Section: Discussionmentioning
confidence: 92%
“…We found that preproCLN5 and proCLN5 are type II transmembrane domain proteins while mature CLN5 (mCLN5) is within the lumen of organelles and localizes to the lysosomal compartment. A recent study also demonstrated a further processing step as mCLN5 is processed in the lysosomal compartment as leupeptin blocked this final processing step [41]. Next to determine whether mCLN5 was soluble or membrane bound, we performed a Na2CO3 extraction and found that a significant portion of mCLN5 is soluble.…”
Section: Discussionmentioning
confidence: 92%
“…While α-syn has been implicated in several cellular processes, including synaptic vesicle endocytosis 24 and exocytosis 25 , its exact function remains unclear. Despite being primarily associated with neurodegenerative disorders, both CLN5 and α-syn can be detected in a variety of tissues and cell types 2631 . While this indicates more general roles of CLN5 and α-syn in non-neuronal tissues, there have been few studies performed to investigate these roles.…”
Section: Introductionmentioning
confidence: 99%
“…In the mouse brain, CLN5 is expressed in cortical neurons, hippocampal pyramidal neurons, hypothalamus, and cerebellum (93); the highest levels, however, have been detected in microglial cells (55,94). CLN5 protein undergoes posttranslational modifications that include glycosylation and cleavage (95,96). The depletion of CLN5 leads to lysosomal degradation of the retromer receptors sortilin and CI-M6PR (62).…”
Section: Neuronal Ceroid Lipofuscinosis and Retromermentioning
confidence: 99%